Synergistic effect of turmeric (Curcuma longa L.) powder and nitrifying probiotics on productivity and ammonia level in excreta from quails (Coturnix coturnix japonica) - Ahmad Junaidi Al Jawawi; Umi Kalsum; Badat Muwakhid (Jurnal Ilmiah Pertanian, 2023)
One of the keys to successful quail rearing is choosing suitable nutritional feed. Unfortunately, feed nutrients not adequately absorbed by the digestive tract of quails, in addition to impacting productivity, will also be wasted and decompose to form ammonia, which becomes a supporting factor for disease. This study aims to determine how adding turmeric powder and nitrifying probiotics affect the productivity and amount of ammonia from quail excreta. The research design used was a completely randomized design (CRD) with 6 (six) treatments, i.e., control (without the addition of turmeric powder and nitrifying probiotics), the addition of nitrifying probiotics 4.5 g/kg of feed, the addition of nitrifying probiotics 6 g/kg of feed, the addition of turmeric powder 3 g/kg of feed, the addition of 3 g turmeric powder + nitrifying probiotics 4.5 g/kg of feed, and the addition of 3 g turmeric powder + nitrifying probiotics 6 g/kg of feed. Data were analyzed statistically using ANOVA and followed by the DMRT. The results showed that adding turmeric powder and nitrifying probiotics had no effect on feed consumption, feed conversion ratio (FCR), protein efficiency ratio (PER), and ammonia level in quail excreta but had a significant impact on quail day production (QDP). This study concluded that adding turmeric powder and nitrifying probiotics can improve the value of QDP, PER, and reduce ammonia levels in quail excreta but had not been able to enhance the value of feed consumption and feed conversion ratio.